Strength Characteristics of Bamboo Reinforced Slabs - Suppiah, S; Agnihotri, S; Mishra, S; Vishwakarma, S (International Journal of Engineering and Technology, 2018)
The construction industry consumes large quantities of composite materials, such as steel, cement and other binding materials. This process emits enormous volume of carbon dioxide leading to global warming and other environmental degradation. As an alternative to steel, bamboo, rattan cane and other agricultural products have been used as reinforcement in different parts of world. However, the application of this non fossil-fuel products has not been exploited to greater extent. In the present study the use of bamboo (bambusa vulgaris) has been adopted as an alternative to steel in fabricating slabs of dimension 1500 mm x 500 mm x 75 mm (length x breadth x thickness). M25 grade with water cement ratio as 0.5 was used. The slabs were tested using Non-Destructive Tests to determine the quality of concrete adopted. Subsequently, destructive tests were carried using a loading frame ofÂ capacity 1000 kN. The non-destructive tests and destructive tests were repeated on steel reinforced slabs and control slabs (without any reinforcement). The results indicate that the bamboo reinforced slabs comparatively weaker with respect to steel reinforced slabs and stronger with respect to control slabs. Therefore, it is recommended to adopt BRC slabs for low cost dwellings. Â Â